"Mōko Shūrai Ekotoba" (Illustrated Account of the Mongol Invasions): A Case Study of Encounter with the Other in Japan - Testa, Giuseppina Aurora (Eikón / Imago, 2020)
This paper is a study of a Japanese illustrated handscroll produced in the late Kamakura period (1185-1333), the Mōko Shūrai Ekotoba, that provides an invaluable pictorial account of the two attempted Mongol invasions of Japan in the years 1274 and 1281. It was copied and restored, with some images significantly altered, during the Edo period (1615-1868). While in the original handscroll the appearances of the foreign Mongols were depicted as accurately as possible, the figures added later show exaggerated features and distortions that correspond to new modes of imagining and representing peoples reflecting a new language and the shifting cosmologies brought about by the Japanese encounter with more “different” Others (Europeans).